ROLE OF THE INSOLVENCY ADMINISTRATOR AND OF THE OFFICIAL RECEIVER IN THE DYNAMICS OF THE CONTRACTS OF DEBTOR IN INSOLVENCY, IN THE REGULATION OF THE INSOLVENCY CODE - Eugenia VOICHECI (Challenges of the Knowledge Society)
On 25 June 2014, the Law no.85/2014 was published in the Official Gazette, that sets forth the rules in the field of preventing insolvency and in the insolvency field itself. A special attention needs to be paid on to the insolvency administrator and the official receiver, deemed by the doctrine in the former doctrine and in the former regulation, as participants in the insolvency procedure participants in the insolvency procedure. This study does not aim to make an exhaustive inventory of the tasks of the duties of the two participants in the insolvency procedure. This study starts from the premises that the insolvency procedure targets the covering of the debtor liabilities, by granting, where possible, the chance of redressing its activity. It starts from an evident ascertainment: namely that, on the date of initiating the insolvency procedure, the debtor’s activity is not interrupted ex abrupto and finally, that it may continue during the observation time, during the reorganization period and even after falling bankrupt. Or, an ongoing activity implies the development of some previously concluded contracts, their denunciation and even the conclusion of some new contracts. Therefore, during the procedure, such dynamics of the debtor contracts is vitally important. In the doctrine focused on the former regulation, the two participants in the procedure were deemed as “justice attorneys”, and in this recent doctrine they were appreciated as “justice representatives”. This study proposes also another approach of the quality of representative of both participants in the procedure, an approach that would emphasize the legal relationships between the insolvency administrator and the official receiver, on one hand and the debtor in insolvency, on the other hand. On other words, the study wants to emphasize where the insolvency administrator and official receiver, depending on the incumbent legal tasks, in relationship with the debtor.